circRNAs: Insight Into Their Role in Tumor-Associated Macrophages - Duan, Saili; Wang, Shan; Huang, Tao; Wang, Junpu; Yuan, Xiaoqing (Frontiers in Oncology, 2021)
Currently, it is well known that the tumor microenvironment not only provides energy support for tumor growth but also regulates tumor signaling pathways and promotes the proliferation, invasion, metastasis, and drug resistance of tumor cells. The tumor microenvironment, especially the function and mechanism of tumor-associated macrophages (TAMs), has attracted great attention. TAMs are the most common immune cells in the tumor microenvironment and play a vital role in the occurrence and development of tumors. circular RNA (circRNA) is a unique, widespread, and stable form of non-coding RNA (ncRNA), but little is known about the role of circRNAs in TAMs or how TAMs affect circRNAs. In this review, we summarize the specific manifestations of circRNAs that affect the tumor-associated macrophages and play a significant role in tumor progression. This review helps improve our understanding of the association between circRNAs and TAMs, thereby promoting the development and progress of potential clinical targeted therapies.